Comparison of methods of correction of stand in bean crops - Fernandes, Maria Imaculada P. S.; Ramalho, Magno A. Patto; Lima, Paulo César (Pesquisa Agropecuaria Brasileira, 2014)
In order to evaluate the influence of loss of plants on the yield of experimental plots, and to compare methods of correction of stand in common bean (Phaseolus vulgaris(L.)) crops, trials with simulation of different proportions of gaps were carried out in Sete Lagoas, MG, in 1983. Two bean cultivars, CNF-005 and Pintado were used, a different trial being set up for each cultivar. The trials were conducted in randomized complete blocks with seven replicates. The number of pods per plant, grain yield per plant, and grain yield in kg/ha were assessed. The results obtained for both cultivars were in agreement, and showed that bean plants have capacity to compensate for the gaps by a greater productivity of the plants situated next to the gaps. This stability in grain yield was explained principally by the number of pads per plant, which showed itself sufficiently plastic to compensate the total grain yield in kg/ha even in the smaller stands. Regarding the methods of correction of the stands, the expression that employed the coefficient of linear regression (b) was shown to be efficient in correcting data of grain yield and its components, whilst the expression of Zuber was equally efficient, but only for grain yield.